Dialoguing with daily life complexity. A Spanish refugee woman under occupied France - Martínez Martínez, Alba (Hispania Nova, 2021)
This article looks into the the years of the Occupation of France based on the analysis of the diary of a young Spanish refugee woman who lived in the occupied zone and maintained a close relationship with the occupiers. We propose to understand how her daily life was articulated under that regime and to what extent gender and her refugee status were significant elements of the power relations she established with the Germans. To this end, we structured our study around four spaces and moments that brought together different images, relationships and ways of understanding the Occupation: the work space, the home and the community, the city of Bordeaux and its places of leisure, and the Liberation. We tried to highlight women's agency in order to deal with an exceptional, contradictory and extremely complex everyday life.
Keywords: occupation; refugee women; daily life; gender; agency